2011
DOI: 10.1111/j.1600-0838.2010.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Could tendinosis be involved in osteoarthritis?

Abstract: Ten patients, age 60 (48-75 years), with osteoarthritis (OA) of the hip and 10 patients, age 82.5 (60-90 years), with fracture of the collum femoris (FCF; minimum Garden stage III) underwent an open biopsy procedure from the internal obturator tendon in conjunction with a total hip replacement. The histological evaluation revealed that all tendon samples in the OA group revealed scar tissue; the corresponding was found in 50% of patients in the FCF group (P=0.02). There were also more GAGs (P=0.023) and calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 46 publications
1
40
1
Order By: Relevance
“…Thus far, strategies that stimulate the complete regeneration of tendons after injury have not been developed. To this end, a better understanding of tendon cell biology is essential to devise improved treatment options for tendon injuries such as tendinopathy [1].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, strategies that stimulate the complete regeneration of tendons after injury have not been developed. To this end, a better understanding of tendon cell biology is essential to devise improved treatment options for tendon injuries such as tendinopathy [1].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, internal obturator tendons removed from osteoarthritic hip joints have significantly more GAGs as well as calcium deposits 33 . These findings implicate swelling of the enthesis that may be an adaptation to increased loading, however this would also result in disruption of the fibrous matrix and effective load transmission.…”
Section: Discussionmentioning
confidence: 99%
“…These findings implicate swelling of the enthesis that may be an adaptation to increased loading, however this would also result in disruption of the fibrous matrix and effective load transmission. Calcium deposition also plays an integral role in OA pathology as mineral aggregation has been shown in the articular cartilage, meniscus, and synovial fluid 24,33,34 . In our study calcium deposits were observed within the LI zone, potentially disrupting fiber organization and undermining mechanical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were evaluated using a semiquantitative (nonparametric) grading system for the tendon alterations used in multiple previous studies. 13 , 17 , 18 , 28 Grading was based on a 4-point scoring system ( Table 1 ). Fiber structure, cellularity, vascularity, and level of GAGs were graded after examining the entire section.…”
Section: Methodsmentioning
confidence: 99%